Ameliorative Efficacy of the Cassia auriculata Root Against High-Fat-Diet + STZ-Induced Type-2 Diabetes in C57BL/6 Mice - Salma, Babu (ACS Omega, 2020)
[Image: see text] Diabetes mellitus is a major metabolic disorder worldwide. Several herbs are being tested for the management of diabetes. Cassia auriculata is one of those herbs known for its nutritional value and health benefits. However, limited scientific evidence has been shown on the elucidation of its root bioactives as well as biological activity. This study attempted to identify and characterize phenolic compounds from the potent root extract and to evaluate its antioxidant as well as antidiabetic properties in both in vitro and in vivo models. The results revealed that the total polyphenol and flavonoid contents were highest in the methanolic extract. The methanolic extract of the C. auriculata root showed the highest antioxidant and antidiabetic activities in vitro than other extracts. These biological activities may be because the extract is rich in coumaric acid and −OH groups as revealed by high-performance liquid chromatography and Fourier-transform infrared spectroscopy analyses, respectively. Further, the antidiabetic activity of the methanolic extract was studied in a diet-induced type-2 diabetes mellitus (T2DM) C57BL/6 mouse model. A significant increase in fasting blood glucose and decreased plasma insulin levels in T2DM mice confirmed the development of the diabetic condition. In addition, the T2DM mice showed oxidative stress in the plasma as well as muscle tissue and significant alterations in the plasma biochemistry, viz., lipid profile, liver, and renal function tests. However, the administration of the ethanolic extract of the C. auriculata root (150 mg/kg body weight) to T2DM mice normalized the condition comparable to that of control mice. Thus, the extract can be used as a potent antioxidant and antidiabetic agent in pharmaceutical companies.